Structure, stability, and electronic properties of pseudomorphic (si)n/(ge)m superlattices - Theodorou, George Os; Tserbak, C.; Kelires, Pantelis C. (My University, 1993)
We investigate the structure, energetics, and electronic properties of (Si)5/(Ge)5 and (Si)3/(Ge)4 superlattices. Our analysis, based on the empirical-potential approach, shows that the thermodynamic stability of these superlattices decreases with increasing substrate lattice constant. Electronic properties are inferred from tight-binding calculations. Use of the interatomic distances obtained here and of those given by elastic theory leads to similar results for the band structure and transition probabilities.
Keywords: Thermodynamics; Electronics